Gestão da informação na administração pública: o caso da prefeitura de Telêmaco Borba - Lemes, Alyne Moreira (2012)
The work aims to analyze how is the process of information management within the Municipality of Telemaco Borba. The proposed observe how the local government arranges his team to maintain effective communication both internally and externally comes to the importance of having an integration between all sectors of local government so that there is an ongoing process and complete arrival distribution and storage of information relevant to City Hall. Considering that the main objective of the GI is to make the information reach the right people at the right time, are considered important steps in this process the search, identification, classification, processing, storage and dissemination of data and, in this context, the study seeks to answer the question below problem: the communication process Prefectural Telemaco Borba contemplates citizens? adheres to the goal of identifying the effectiveness or ineffectiveness of Information Management within the City of Telemaco Borba and observe and describe how this work is developed by Public Administration is implementing a new project communication within their structures.